Determinants of risk tolerance on financial asset ownership: a case of Malaysia - Duasa, Jarita; Abdullah Yusof, Selamah (Universiti Malaysia Sarawak, 2013)
The present study intends to shed new light on the issue of determinants of risk tolerance among Malaysians using data obtained from a survey. The main analysis is based on ordinary least square (OLS) method of regression using level of financial risk tolerance as the dependent variable and socio–economic factors as regressors. The preliminary analyses found that majority of the respondents prefer to keep their money in liquid assets, such as in saving account and cash. These assets definitely have the lowest level of risk compared to other forms of assets. A further analysis, using OLS regression reveals several significant determinants of risk tolerance among the sample respondents. Risk tolerance is higher among the young, males, those with higher level of education and those in non-public sector. In addition, the study also finds that Malays are more risk averse than Chinese and those in Kedah are more risk averse than those in Kuala Lumpur.